2002
DOI: 10.1159/000048210
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Cholinesterase Activity after Intravenous, Oral or Dermal Administration of Methyl Parathion

Abstract: Time-dependent changes in blood cholinesterase activity caused by single intravenous, oral or dermal administration of methyl parathion to adult female rats were defined. Intravenous and oral administration of 2.5 mg/kg methyl parathion resulted in rapid (<60 min) decreases in cholinesterase activity which recovered fully in vivo within 30–48 h. In contrast, spontaneous reactivation of cholinesterase in vitro was complete within 6 h at 37°C. Dermal administration of methyl parathion caused dose-dependent inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Methyl parathion was administered to adult female rats via intravenous, oral and dermal routes, and it was found that dermal administration of methyl parathion resulted in a dose-dependent inhibition of acetylcholinesterase that developed slowly and was prolonged; however, intravenous and oral administration of methyl parathion resulted in rapid decreases in cholinesterase activity which was later fully recovered within 30-48 hours [67]. This supports the claim that dermal exposure to methyl parathion is more effective than other routes of exposure.…”
Section: Neurotoxic Effectssupporting
confidence: 53%
“…Methyl parathion was administered to adult female rats via intravenous, oral and dermal routes, and it was found that dermal administration of methyl parathion resulted in a dose-dependent inhibition of acetylcholinesterase that developed slowly and was prolonged; however, intravenous and oral administration of methyl parathion resulted in rapid decreases in cholinesterase activity which was later fully recovered within 30-48 hours [67]. This supports the claim that dermal exposure to methyl parathion is more effective than other routes of exposure.…”
Section: Neurotoxic Effectssupporting
confidence: 53%
“…In vivo, the intravenous or oral administration of 2.5 mg/kg of methylparathion, drop it in under 60 min and the reactivation of cholinesterase is 30-48 h in vitro. The spontaneous reactivation of cholinesterase is complete after 6 h at 37°C [5]. Dermal inhibition of cholinesterase activity of methyl parathion is dose dependent.…”
Section: Discussionmentioning
confidence: 97%
“…The pharmacodynamic properties of some of these products, including methyl parathion and the kinetics of cholinesterase activity in the brain, parallel to the plasma activity depend on the route of administration of the toxicant [5].…”
Section: Discussionmentioning
confidence: 99%
“…Kramer et al [10] compared that pharmacodynamics of methyl parathion based on the route of exposure. The underlying mechanism for its toxicity in humans is the inhibition of acetylcholinesterase by its oxidative metabolite, methyl paraoxon [ 11 ].…”
Section: Dermal Exposure To Methyl Parathion Poses the Greatest Heakhmentioning
confidence: 99%